The Influence of Synectics, Mind Mapping, Cooperative Learning (SM2CL) Models on Creative Thinking Skills and Understanding of Nutritional Concepts in Digestive System Material in Students - Lisra Pratama; A. Mushawwir Taiyeb; Rachmawaty (Postgraduate, University of Mataram, 2026)
This study aims to determine the effect of the Synectics, Mind Mapping, Cooperative Learning (SM2CL) learning model on creative thinking skills and understanding of the concept of the human digestive system in class XI students of MAN 3 Bone. This type of research is a quasi-experimental study with a quantitative approach. The research design is a pretest-posttest control group design. The population in the study were all class XI students in the 2025/2026 academic year who were spread into 2 study groups. The sampling technique used was non-probability sampling, namely saturation sampling. A total of 2 study groups were used in this study, namely, study group XI A5 as the experimental class applied the SM2CL model and study group XI A6 as the control class applied the Direct Instruction model. Based on the results of the Ancova test, the significance value of the creative thinking skills variable was 0.001 < 0.05 and the significance value of understanding learning concepts was 0.041 < 0.05, so it can be concluded that the application of the synectics, mind mapping, cooperative learning (SM2CL) learning model has a significant or real effect on creative thinking skills and understanding concepts in class XI students of MAN 3 Bone.